Uncertainties of the heart: The History and the world of emotions - de la Pascua Sánchez, María José (Cuadernos de Historia Moderna, 2015)
In this article I use a methodology to bring history´s emotions closer to the experience of love from the analysis of diverse sources (epithalamios, spiritual and philosophical works, courtesan and sentimental novels, inquisitorial records, letters) that constitute deposits of discursive praxis of loving culture of the Fifteenth to Eighteenth Centuries. It also suggest a parallel analysis of the love practices that takes into account the specificity the sense of time in emotional experiences and the context of daily life that gives them meaning and significance.